Optimizing iron absorption to achieve iron adequacy for children’s growth and development - Widjaja Lukito (World Nutrition Journal, 2020)
Iron nutrition plays important roles in human health. In many developing countries, iron deficiency, caused by many factors, prevails. One well-documented clinical form of iron deficiency is iron-deficiency anemia (IDA).